MANAGEMENT OF PROCESSES IN FOOD PRODUCTION - Mamajonova Sarvinozxon Odiljon qizi; Shoymatova Xolida Qudrat qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abctract Efficient management of production processes in the food industry is critical for ensuring  product  quality,  safety,  and  economic  efficiency.  The  thesis  discusses methods  for  process  control,  technological  integration,  and  personnel  management within modern food manufacturing. Key innovations, including automation and IoT technologies,  are  explored,  alongside  Lean  management  principles  for  operational improvement.